Left Internal Mammary Artery Injury Requiring Resuscitative Thoracotomy: A Case Presentation and Review of the Literature. (11th November 2012) - Al Hassani, Ammar; Abdul Rahman, Yassir; Kanbar, Ahad; El-Menyar, Ayman; Al-Aieb, Abubaker; Asim, Mohammad; Latifi, Rifat
Abstract : Background . Penetrating injuries to the chest and in particular to the heart that results in pericardial tamponade and cardiac arrest requires immediate resuscitative thoracotomy as the only lifesaving technique and should be performed without delay. Objective . To describe an external cardiac tamponade caused by massive tension hemothorax from penetrating injury of the left internal mammary artery (LIMA). Method . A case presentation treated at the Level I trauma center at Hamad General Hospital, in Doha, Qatar and review of the literature on LIMA injuries reported cases. Results . LIMA injury as a cause of hemothorax is not uncommon, but to our knowledge our case is the first massive tension hemothorax with witnessed cardiac arrest reported in the literature requiring emergency thoracotomy, performed in trauma room, with full recovery. Conclusion . Injury to the LIMA with massive tension hemothorax requires immediate resuscitative thoracotomy.